Theory of Mind as a Mediator Between Emotional Trust Beliefs and Interpersonal Communication Competence in a Group of Young Adults. Issue 2 (April 2021) - Petrocchi, Serena; Filipponi, C.; Antonietti, C.; Levante, A.; Lecciso, F.
Research has provided direct and indirect evidence of associations between trust beliefs and social-perceptual theory of mind (ToM) and between social-perceptual ToM and interpersonal communication competence during childhood and adolescence. This research (a) developed a scale for evaluating trust beliefs in young Italian adults (Study 1) and (b) examined how social-perceptual ToM mediates the relationship between emotional trust beliefs and interpersonal communication competences such as assertiveness and empathy (Study 2). In Study 1, a sample of 168 university students ( M  = 23.3, SD  = 3 months) completed the Italian Adults' Generalized Trust Beliefs (AGTB) scale and two second-order false beliefs tasks. In Study 2, 318 Italian university students ( M  = 22.96 years, SD  = 2 months) completed the AGTB scale, the Experiences in Close Relationships-Revised questionnaire, the Reading the Mind in the Eyes Test, and items measuring assertiveness and empathy. As expected, the AGTB scale exhibited acceptable internal consistency, structural validity, and construct validity. Furthermore, path analysis confirmed the existence of the hypothesized paths between adults' emotional trust beliefs, social-perceptual ToM, assertiveness, and empathy. This study also identified the effects of gender on the other variables, but sex did not moderate the relationships between variables.